1991
DOI: 10.1111/j.1365-2648.1991.tb01596.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse socialization: issues and problems

Abstract: A comparative study was conducted of the professional socialization process of student nurses in three nurse education centres in South Wales. Patterns and problem areas can be identified of relevance to issues in role theory and with practical implications for the more effective implementation of Project 2000. Three cohorts of students were interviewed using a semi-structured interview schedule whilst in the introductory block and at the end of the first year. The teaching and ward staff directly involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 8 publications
5
31
0
Order By: Relevance
“…An account of the process of professional socialization from the perspective of students undergoing the HE diploma in nursing course has been provided. This study differs from previous longitudinal studies which have either focused on traditional students ( Simpson 1967, Seed 1991, Wilson & Startup 1991) or degree students ( Davis 1975, Day et al . 1995 ) or have failed to follow either traditional ( Melia 1981) or Project 2000 students throughout their course ( Bradby & Soothill 1993, O'Neill et al .…”
Section: Discussionmentioning
confidence: 67%
“…An account of the process of professional socialization from the perspective of students undergoing the HE diploma in nursing course has been provided. This study differs from previous longitudinal studies which have either focused on traditional students ( Simpson 1967, Seed 1991, Wilson & Startup 1991) or degree students ( Davis 1975, Day et al . 1995 ) or have failed to follow either traditional ( Melia 1981) or Project 2000 students throughout their course ( Bradby & Soothill 1993, O'Neill et al .…”
Section: Discussionmentioning
confidence: 67%
“…(See for example, the accounts of Wilson and Startup (1991), Elkan and Robinson (1993), Gray and Smith's (1999) for project reforms (the change in programme where the training moved from hospitals to being taught in Universities) and Andrew et al (2009), Melling (2011, and Leducq et al (2012) for post curricular reforms). Nevertheless, some authors continue to report that student' experiences of the ideals of clinical practice still fall short of the academic content of student's programmes (Astin et al, 2005).…”
Section: Background/literaturementioning
confidence: 99%
“…[4][5][6]8 Although research relative to professional socialization during students' professional preparation years is limited in athletic training, [9][10][11] investigators have suggested that various determinants positively or negatively affect the professional socialization and developing identity of preservice students in other fields. [1][2][3][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Relative to athletic training, Pitney 5 and Pitney et al 6 described a need to study the effect of student socialization during the undergraduate athletic training education experience. Stevens et al 8 determined the perceived role of clinical and field experiences during the professional preparation period in the professional socialization of entry-level athletic trainers (ATs).…”
mentioning
confidence: 99%